Correlation between NLR and PLR with the Severity of COVID-19 Inpatients - Fitriana Andiani; Rita Herawati; Yani Triyani (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
When the COVID-19 outbreak is ongoing, the classification of COVID-19 patients based on the severity assessment is necessary to optimize the allocation of existing resources and early management interventions to improve prognosis. Neutrophil-to-Lymphocyte Ratio (NLR) and Platelet-to-Lymphocyte Ratio (PLR) are two of the most common, simple, inexpensive, rapid, and widely available tests in all health facilities, which indirectly indicate the inflammatory status of COVID-19 patients. This study aimed to analyze the correlation between NLR and PLR with the severity of COVID-19 inpatients. This cross-sectional study was conducted retrospectively using medical record data of COVID-19 patients hospitalized at Al Islam Hospital, Bandung, from January to March 2021. COVID-19 patients involved in this study were classified into moderate, severe, and critical degrees. Statistical analysis was carried out using ANOVA or Kruskal-Wallis and Spearman with a significant value of p < 0.05. The median NLR and PLR results based on the severity were 3.49; 6.27; 8.4 (p<0.001) and 159.2; 202.6; 250.9 (p<0001), respectively. There was a correlation between NLR and PLR and the severity with r= 0.415 (p<0.001) and r=0.216 (p<0.001), respectively. The correlation between NLR and the severity was stronger than PLR. Therefore, it was concluded that there was a correlation between NLR and PLR with the severity of COVID-19 patients.